Evaluation of Phytoremediation Potential of Rose Species - TURAN, METIN; ERCISLI, SEZAI (Asian Journal of Chemistry, 2010)
The use of plants to remove heavy metals from soil (phytoremediation) is emerging as a cost-effective to conventional methods. The objective of this study was to investigate heavy metal uptake capacity of fruit flesh and seeds of 6 rose species (Rose canina, Rosa dumalis subsp. boissieri, Rosa dumalis subsp. antalyensis, Rosa villosa subsp. villosa, Rosa pisiformis and Rosa pulverulenta) of same age from a collection orchard in Erzurum city, Eastern part of Turkey. Results indicated that significant differences were found in terms of heavy metal uptake among species and fruit parts. Among species tested, Rosa pulverulenta were more effective for Cd, Al and Si uptake and Rosa dumalis subsp. boissieri for Ni uptake. According to results, Rosa pulverulenta could be useful for remediation of heavy metal from Cd, Al and Si contaminated area.